High pressure crystal structure and electrical properties of a single component molecular crystal [Ni(dddt)2] (dddt = 5,6-dihydro-1,4-dithiin-2,3-dithiolate) - Cui, H; Tsumuraya, T; Yeung, HH-M; Coates, CS; Warren, MR; Kato, R (MDPI, 2019)
Single-component molecular conductors form an important class of materials showing exotic quantum phenomena, owing to the range of behavior they exhibit under physical stimuli. We report the effect of high pressure on the electrical properties and crystal structure of the single-component crystal [Ni(dddt)2] (where dddt = 5,6-dihydro-1,4-dithiin-2,3-dithiolate). The system is isoelectronic and isostructural with [Pd(dddt)2], which is the first example of a single-component molecular crystal that exhibits nodal line semimetallic behavior under high pressure. Systematic high pressure four-probe electrical resistivity measurements were performed up to 21.6 GPa, using a Diamond Anvil Cell (DAC), and high pressure single crystal synchrotron X-ray diffraction was performed up to 11.2 GPa. We found that [Ni(dddt)2] initially exhibits a decrease of resistivity upon increasing pressure but, unlike [Pd(dddt)2], it shows pressure-independent semiconductivity above 9.5 GPa. This correlates with decreasing changes in the unit cell parameters and intermolecular interactions, most notably the π-π stacking distance within chains of [Ni(dddt)2] molecules. Using first-principles density functional theory (DFT) calculations, based on the experimentally-determined crystal structures, we confirm that the band gap decreases with increasing pressure. Thus, we have been able to rationalize the electrical behavior of [Ni(dddt)2] in the pressure-dependent regime, and suggest possible explanations for its pressure-independent behavior at higher pressures.